THE HERITAGE OF PERSONAL BOOK COLLECTIONS IN THE WRÓBLEWSKI LIBRARY OF THE LITHUANIAN ACADEMY OF SCIENCES - LIUDAVIČIENĖ, DAIVA; VENCLOVIENĖ, ANA (Knygotyra, 2012)
Based on the collection management practices established in the Wróblewski Library of the Lithuanian Academy of Sciences, the article deals with problems that arise in managing personal collections and seeking to bring them to readers’ attention. The article outlines how collection management is carried out in the Wróblewski Library and describes different methods used to foster access to three of the more valuable collections. It is stated that presenting a personal collection as an entirety on the library’s web page partly solves issues that arise when publications from a single collection are dispersed into different holdings due to shortage of space. The case when a library presents a collection whose books are physically kept not in the library (in this case a virtual catalogue of the collection is to be created) is the subject of a separate discussion.
Keywords: ...